TINJAUAN PENERAPAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA RESTORAN X - Asaprima Putra Karunia; Ismul Aksan (Jurnal Akuntansi dan Pajak, 2025)
The aims of this study are to suggest the implementation of EOQ method for inventory management in restaurant X. This study make use of descriptive qualitative method using purchasing and sales data within 2023. This study finds that the implementation of EOQ will reduce Total Inventory Cost of the restaurant for 67%. This method also bring positive imrovement to the restaurant by enabling the use of safety stock and reorder point. This will eliminate the uncertanty surrounding inventory management.